Node Localization in Wireless Sensor Networks Using Butterfly Optimization Algorithm - Arora, Sankalap; Singh, Satvir (Arabian journal for science and engineering (2011), 2017)
Accurate localization of sensor nodes has a strong influence on the performance of a wireless sensor network. In this paper, a node localization scheme using the application of nature-inspired metaheuristic algorithm, i.e., butterfly optimization algorithm, is proposed. In order to validate the proposed scheme, it is simulated on different sizes of sensor networks ranging from 25 to 150 nodes whose distance measurements are corrupted by gaussian noise. The performance of the proposed novel scheme is compared with performance of some well-known schemes such as particle swarm optimization (PSO) algorithm and firefly algorithm (FA). The simulation results indicate that the proposed scheme demonstrates more consistent and accurate location of nodes than the existing PSO- and FA-based node localization schemes.